Mali : 2015 Article IV Consultation, Fourth Review Under the Extended Credit Facility Arrangement, and Request for Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Mali's program performance through June was strong, with all performance criteria and most structural benchmarks met. The 2016 program features a somewhat higher fiscal deficit compared with 2015 to allow for increased public investment and reconstruction spending. The program's structural component incorporates measures to support continued revenue growth, strengthen public financial management, and promote good governance. The external current account is projected to strengthen in the near term but would weaken thereafter, mainly as a result of less favorable terms of trade.